Enhanced Efficiency for Dye-Sensitized Solar Cells with Metal Oxide Modified SnO2 Photoanodes. Issue 1 (March 2021) - Fan, Hao; Zou, Shibing; Yang, Hao; Duan, Junhong; Liu, Weiqing; Wu, Huaming
Abstract: In this work, mesoporous SnO2 photoanode was modified using a hydrolysis method with AlCl3, MgCl2, ZrOCl2 aqueous solutions, respectively. Four kinds of DSCs with SnO2, SnO2 /Al2 O3, SnO2 /MgO, SnO2 /ZrO2 as photoanode were fabricated, respectively. The photovoltaic performance of DSCs modified by AlCl3 and MgCl2 aqueous solutions was improved observably, especially in V oc, while the ZrOCl2 treatments give a negligible influence. Furthermore, the cells are evaluated once at the interval of three days within 30 days after fabrication. The V oc of four kings of cell is gradually improved, while J sc is hardly changed during testing. The PCE of SnO2, SnO2 /Al2 O3, SnO2 /MgO, SnO2 /ZrO2 DSCs increases form 1.55, 1.87, 1.77, 1.63% at beginning to 4.03, 4.92, 5.04, 4.48% at stable, respectively. For modified photoanodes, chemical capacitance C μ decreases and transfer resistance R ct increases by EIS measurements, which confirm further facilitate charge extraction and suppress charge recombination.